2013
DOI: 10.1002/pam.21699
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Pension Systems, the Composition of the Teaching Workforce, and Teacher Quality

Abstract: Teacher pension systems concentrate retirements within a narrow range of the career cycle by penalizing individuals who separate too soon or remain employed too long. The penalties result in the retention of some teachers who would otherwise choose to leave, and the premature exit of some teachers who would otherwise choose to stay. We examine the link between teachers’ pension incentives and workforce quality and find no evidence to suggest that the incentives raise quality. Given the large and growing costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Differences between both public employee retiree health insurance plans and the other types of insurance studied and public and private employees suggest the effects of retiree health insurance may be different across the public and private sectors. For example, research has shown that public sector employees are particularly responsive to the nonlinearities in their pension benefits (Costrell and Podursky 2009; Brown 2010; Koedel et al 2013; Grissom et al 2013a, 2013b) and are more knowledgeable about their retirement benefits (DeArmond and Goldhaber 2010) than their counterparts in the private sector.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between both public employee retiree health insurance plans and the other types of insurance studied and public and private employees suggest the effects of retiree health insurance may be different across the public and private sectors. For example, research has shown that public sector employees are particularly responsive to the nonlinearities in their pension benefits (Costrell and Podursky 2009; Brown 2010; Koedel et al 2013; Grissom et al 2013a, 2013b) and are more knowledgeable about their retirement benefits (DeArmond and Goldhaber 2010) than their counterparts in the private sector.…”
Section: Introductionmentioning
confidence: 99%
“…Three papers build on the peak value approach in Coile and Gruber (2007) by measuring differential responses among teachers: Costrell and McGee (2010), Friedberg andTurner (2011), andKoedel, Podgursky, andShi (2013). Costrell and McGee (2010) estimate peak value models for Arkansas teachers and find that teachers are indeed responsive to peak value.…”
Section: My Contributions and Review Of The Literaturementioning
confidence: 99%
“…I also look at the differences in retirement behavior by teacher value-added, and I find that high-value-added teachers are the least likely to leave during the pension pull but behave similarly to low-valueadded teachers during the pension push. Koedel, Podgursky, and Shi (2013) examine the relationship between value-added and retirement, but through a different lens. They do not leverage variation in pension wealth or peak value, but instead use peak value to determine teacher type.…”
Section: My Contributions and Review Of The Literaturementioning
confidence: 99%
“…Differences between both public employee retiree health insurance plans and the other types of insurance studied and public and private employees suggest the effects of retiree health insurance may be different across the public and private sectors. For example, research has shown that public sector employees are particularly responsive to the nonlinearities in their pension benefits (Costrell and Podursky 2009;Brown 2010;Koedel et al 2013;Grissom et al 2013b) and are more knowledgeable about their retirement benefits (DeArmond and Goldhaber 2010) than their counterparts in the private sector.…”
Section: Introductionmentioning
confidence: 99%